Deep Brain Stimulation in Drug Addiction Treatment: Research Progress and Perspective - Chang, Rui; Peng, Jionghong; Chen, Yunfan; Liao, Hailin; Zhao, Size; Zou, Ju; Tan, Sijie (Frontiers in Psychiatry, 2022)
Drug addiction is a chronic psychiatric disorder characterized by compulsive drug-seeking and drug-using behavior, and a tremendous socioeconomic burden to society. Current pharmacological and psychosocial methods have shown limited treatment effects for substance abuse. Deep Brain Stimulation (DBS) is a novel treatment for psychiatric disease and has gradually gained popularity in the treatment of addiction. Addiction is characterized by neuroplastic changes in the nucleus accumbens (NAc), a key structure in the brain reward system, and DBS in this region has shown promising treatment effects. In this paper, the research progress on DBS for drug addiction has been reviewed. Specifically, we discuss the mechanism of NAc DBS for addiction treatment and summarize the results of clinical trials on DBS treatment for addiction to psychoactive substances such as nicotine, alcohol, cocaine, opioids and methamphetamine/amphetamine. In addition, the treatment effects of DBS in other brain regions, such as the substantia nigra pars reticulata (SNr) and insula are discussed.